STRATEGI PEMASARAN DALAM UPAYA MENINGKATKAN PENDAPATAN PADA DIVA KARAOKE RUMAH BERNYANYI DI KOTA TIMIKA - Augusti Gesta Nabilla; Antje Tuasela (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2021)
This study aims to determine the analysis of marketing strategies to increase income for singing karaoke divas in Timika City. The research method used in this research is descriptive method. Data collection techniques were carried out by means of observation, questionnaires, documentation, and literature studies. The analytical instrument used is SWOT analysis. The results of this study indicate that the analysis of marketing strategies to increase income for singing karaoke divas in the city of Timika lies in quadrant I of the SO strategy, which has alternative strategies such as adequate services, promotional offers and providing a place or location.